On the spectrum of one dimensional p-Laplacian for an eigenvalue problem with Neumann boundary conditions - Dakkak, Ahmed; El Habib, Siham; Tsouli, Najib (Boletim da Sociedade Paranaense de Matemática, 2015)
This work deals with an indefinite weight one dimensional eigenvalue problem of the p-Laplacian operator subject to Neumann boundary conditions. We are interested in some properties of the spectrum like simplicity, monotonicity and strict monotonicity with respect to the weight. We also aim the study of zeros points of eigenfunctions.